Pelayanan Terhadap Penyandang Disabilitas UPTD Balai Rehabilitasi Terpadu Penyandang Disabilitas Dinas Sosial DIY Tahun 2017-2019 - Davinia Farah Salwahanan; Ane Permatasari (Universitas Teuku Umar, 2020)
The Integrated Rehabilitation of Persons with Disabilities of the DIY Social Service is to provide a livelihood and a decent life for the disabled. The discussion of the diffable is felt to be very isolating the movement of the diffable to access public services especially in public. The granting of rights for persons with disabilities has been regulated in Law Number 8 of 2016 concerning Persons with Disabilities and regulated in DIY Regulation Number 4 of 2012 governing the protection and fulfillment of the rights of persons with disabilities. The results of the study showed that the services provided at the UPTD Integrated Rehabilitation Center for Persons with Disabilities of the Social Service DIY provided a one-stop service. This can be a place for people with disabilities to channel their talents in Vocational Guidance and can improve themselves so that they can be social like the general public.